EXAMINING THE INTERPLAY OF LANGUAGE LEARNING STRATEGIES, GRAMMATICAL COMPETENCE, AND WRITING PERFORMANCE IN EFL HIGHER EDUCATION - Septarini, Dian; Agustiani, Indah Windra Dwie (Universitas Muhammadiyah Palembang, 2026)
This study investigated the relationships among language learning strategies, grammar mastery, and writing achievement among undergraduate students in an English Education program. Employing a correlational design, the study involved 149 students selected through purposive sampling. Data were collected using a questionnaire and a writing test, and analysed through Pearson product-moment correlation and regression analysis. The findings revealed that language learning strategies had no significant relationship with students’ writing achievement. In contrast, grammar mastery showed a significant positive relationship and contributed meaningfully to writing performance. Furthermore, when examined simultaneously, language learning strategies and grammar mastery jointly influenced writing achievement; however, only grammar mastery emerged as a significant predictor. These findings suggest that while language learning strategies alone may not directly impact writing outcomes, grammatical competence plays a more substantial role in supporting students’ writing achievement in an EFL context.